'It's always difficult when it's family. . . whereas when you're talking to a therapist. . .': Parents' views of cognitive-behaviour therapy for depressed adolescents. (October 2021) - Schlimm, Katharina; Loades, Maria; Hards, Emily; Reynolds, Shirley; Parkinson, Monika; Midgley, Nick
Background: Parents are key to helping their adolescent child access psychological therapy for mental health problems such as depression. However, little is known about how parents experience their child's psychological therapy. We aimed to explore parents' experiences of their adolescent child's cognitive behaviour therapy for depression. Method: We applied Thematic Analysis (TA) to qualitative data from in-depth interviews with parents ( N = 16) whose adolescent child was randomly allocated to CBT in a large multisite RCT for adolescent depression (the IMPACT trial). Interviews were conducted at the end of treatment. Results: We generated two main themes: parents' perceptions of the adolescent's journey through therapy, and parents' perceptions of the therapeutic setting and process. Each included four sub-themes. Parents talked about key factors that impacted on their child's progress through treatment, including the adolescent's readiness for therapy and the adolescent-therapist relationship. Conclusion: Parents' insights confirm the foundations of what is considered good clinical practice of CBT for adolescent depression, including tailoring therapy to the adolescent, and establishing a strong adolescent-therapist relationship. Parents recognised that, for CBT to be helpful, their child had to be willing to engage in therapy and able to develop a trusting relationship with their therapist.